What will libraries be doing in 15 years - Anglada, Lluís (Anuario ThinkEPI, 2012)
It seems clear that today libraries still have a clear purpose, but will this also be true in 15 years? This note takes an affirmative stand, that libraries have a future and it is in providing places where people can get in touch with information and socialize, in paying the costs of quality information services for a broad public and in being the institutions that take responsibility for maintaining current information for present and future use.
Keywords: Libraries; Future; Information subsidize; Library as space; Information preservation.